2020
DOI: 10.3389/fpsyg.2020.548755
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Neurocognitive Effects From the Unique Bilingual Experiences of Interpreters

Abstract: For bilinguals, research suggests that both languages are constantly active and competing in the mind, even when only using one. However, this body of work has reported inconclusive results on the long-term effects of the constant parallel activation and use of more than one language on the brain. This has mostly been due to inconsistent comparisons between groups of bilinguals and monolinguals. Not all bilingualisms are the same. The investigation of the use of more than one language over a lifetime offers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The psycholinguistic explanation to this is that the demands of bilingualism call for greater use of working memory (Grundy and Timmer, 2016 ), task switching (Prior and MacWhinney, 2010 ), and inhibitory control (Hartanto and Yang, 2019 )—subsets of executive functions assumed to play a role in fostering the brain's cognitive reserve in old age (Guzmán-Vélez and Tranel, 2015 ). The bilingual advantage hypothesis is not unchallenged, however, as some empirical researchers failed to observe a statistically significant bilingual cognitive advantage in their studies, even for professional simultaneous interpreters (Paap, 2019 ; Ferreira et al, 2020 ). Reasons accounting for this contradiction are manifold:…”
Section: The Bilingual Advantage Debate and Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The psycholinguistic explanation to this is that the demands of bilingualism call for greater use of working memory (Grundy and Timmer, 2016 ), task switching (Prior and MacWhinney, 2010 ), and inhibitory control (Hartanto and Yang, 2019 )—subsets of executive functions assumed to play a role in fostering the brain's cognitive reserve in old age (Guzmán-Vélez and Tranel, 2015 ). The bilingual advantage hypothesis is not unchallenged, however, as some empirical researchers failed to observe a statistically significant bilingual cognitive advantage in their studies, even for professional simultaneous interpreters (Paap, 2019 ; Ferreira et al, 2020 ). Reasons accounting for this contradiction are manifold:…”
Section: The Bilingual Advantage Debate and Dementiamentioning
confidence: 99%
“…Firstly, bilingualism itself is a complex phenomenon and hard to define strictly, being more of a continuous variable than a dichotomous one (Ferreira et al, 2020 ). As Heredia et al ( 2020 ) caution, research has not yet firmly established the moderators and mediators in the bilingual benefits leading to cognitive reserve, which can be empirically problematic.…”
Section: The Bilingual Advantage Debate and Dementiamentioning
confidence: 99%
“…A longitudinal research paradigm should be designed to include two groups of experienced older SIs, one which is still actively practicing simultaneous interpretation (experimental group), while the other one is not (control group). Both groups should be matched for factors potentially influencing outcome measures (i.e., cognition and neuroanatomy) such as age, sex, years of training, years and frequency of professional experience, type of intercepting (Ferreira et al 2020), education, relevant health-related variables (e.g., degree of hearing impairment), and multilingual experience (e.g., age of L2 acquisition, frequency of language use, etc. ; for a continuous and multidimensional manner to describe multilingual experience see also Gullifer et al 2021).…”
Section: Future Directions For Studies On Sis In the Field Of Agingmentioning
confidence: 99%
“…Hence, the bilingual experience using domain-specific cognitive control may over time modify the neural mechanisms underlying these cognitive processes and thus transfer to domain-general cognitive control (DeLuca et al, 2019;Luk et al, 2020;Olguin et al, 2019). Some bilinguals use their language skills professionally, and research on simultaneous interpreters has shown substantial short-term training on working memory and shifting, and long-term effects yielding a neuroanatomical and neurofunctional profile (for review, see Ferreira et al, 2020).…”
Section: Consequences Of Bilingualism On Cognitive Developmentmentioning
confidence: 99%